Ideologia dżucze w wybranych dokumentach polskiej dyplomacji z lat osiemdziesiątych z zasobu Archiwum Akt Nowych i Archiwum Instytutu Pamięci Narodowej - Benken, Przemysław (Komunizm: System - Ludzie - Dokumentacja, 2023)
The goal of this article is to present the main aspects concerning cultural and historical determinants of the Democratic People’s Republic of Korea’s political systemas they were described in selected Polish foreign policy documents from the 1980s. Amongst everything else, the article describes the great importance of the Juche (selfreliance) ideology and Kim’s personality cult (including the “Great Leader” theory) to the Communist regime, which did not develop in a cultural void, but adapted to the so-called “local specificity.”